Enhancing Mathematical Understanding Through Ethnomathematics: A Study Of The Pusaka Monument's Geometric Structures - Atikah Mufidah; Ishartono, Naufal; Masduki, Masduki (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
Several previous studies have examined the ethnomathematical exploration of cultural sites. However, there has been no research specifically exploring the Tugu Pusaka. This study explores the ethnomathematics found in the Pusaka Monument in Selogiri, Wonogiri Regency. Ethnomathematics examines how cultural groups understand and use mathematical concepts. The Pusaka Monument, with its geometric structure, offers numerous aspects for study within this context. The objective of this research is to describe the mathematical concepts present in the Pusaka Monument and to integrate these concepts into mathematics education. The research employs a survey method conducted at the Pusaka Monument site, with purposive sampling to ensure relevance and significance. The study follows a series of steps: literature review, field data collection, and descriptive and factual analysis of findings. Data collection involved observation, interviews, and documentation. The data were analyzed qualitatively, focusing on identifying geometric concepts within the monument's structure. This research aims to enhance students' understanding of mathematics through the integration of cultural elements and to promote the preservation of Indonesia's cultural heritage through ethnomathematics. The findings are expected to contribute to the development of a more contextual and culturally-based mathematics curriculum, enriching both mathematical education and cultural awareness among students. Keywords: Ethnomatematika, Mathematics Education, Pusaka Monument Selogiri, Cultural Heritagez